Strength and stiffness parameters for hardening soil model of rockfill materials - Sukkarak, Raksiri; Likitlersuang, Suched; Jongpradist, Pornkasem; Jamsawang, Pitthaya (Soils and Foundations, 2021)
In recent years, an increasing number of rockfill dams have been constructed in many developing countries around the world. One difficulty in the engineering design and construction of rockfill dams is the characterisation of the rockfill materials. Thanks to advancements in computational geomechanics, a finite element analysis is usually employed in geotechnical engineering design. To perform such analyses, a proper constitutive model with relevant parameters that reflect the stress–strain-strength characteristics of rockfill materials are required. This study presents a procedure to determine the strength and stiffness parameters of rockfill materials that can be used with the Hardening Soil (HS) model to characterise the behaviour of rockfill materials. Based on triaxial and oedometer test results, a set of HS model parameters can be determined. To implement and validate the procedure, six rockfill materials from the Nam Ngum 2 Dam construction project in Laos PDR are employed in this study. The influences of stress level and particle breakage on the stress–strain/volumetric-strain behaviours of rockfill materials are discussed. Finally, the procedure to determine the material parameters for rockfill materials presented in this study can also be applied to other rockfill materials.